2012
DOI: 10.3390/molecules170910322
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Synergy of Berberines with Antibacterial Agents against Clinical Multi-Drug Resistant Isolates of Methicillin-Resistant Staphylococcus aureus (MRSA)

Abstract: Antibacterial activity of berberine (Ber) and 8-acetonyl-dihydroberberine (A-Ber) alone and combined uses with antibacterial agents ampicillin (AMP), azithromycin (AZM), cefazolin (CFZ) and levofloxacin (LEV) was studied on 10 clinical isolates of SCCmec III type methicillin-resistant Staphylococcus aureus (MRSA). Susceptibility to each agent alone was tested using a broth microdilution method and the chequerboard and time-kill tests for the combined evaluations, respectively. The alone MICs/MBCs (μg/mL) range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…The antioxidant capacity of berberine has demonstrated both direct (Jang et al, 2009;Bashir and Gilani, 2011) and indirect activities (Hwang et al, 2002;Tan et al, 2007). Recently, berberine has been structurally modified to yield new derivatives which are able to improve their biological functions: antibacterial (Zuo et al, 2012;Zhang et al, 2013), antifungal (Liu et al, 2014), antiprotozoal (Bahar et al, 2011), and anticancer activities (Zhang et al, 2012;Lo et al, 2013).…”
Section: Antioxidant Effect Of Berberine and Its Phenolic Derivativesmentioning
confidence: 99%
“…The antioxidant capacity of berberine has demonstrated both direct (Jang et al, 2009;Bashir and Gilani, 2011) and indirect activities (Hwang et al, 2002;Tan et al, 2007). Recently, berberine has been structurally modified to yield new derivatives which are able to improve their biological functions: antibacterial (Zuo et al, 2012;Zhang et al, 2013), antifungal (Liu et al, 2014), antiprotozoal (Bahar et al, 2011), and anticancer activities (Zhang et al, 2012;Lo et al, 2013).…”
Section: Antioxidant Effect Of Berberine and Its Phenolic Derivativesmentioning
confidence: 99%
“…But the latest researches confirmed that a five-days AZM therapy could increase the risk of cardiovascular death and the effect of AZM on hERG current remains still unclear (Ray et al, 2012;Svanstrom et al, 2013). In recent years, some researches proved that use of BBR combined with antibacterial agents (azithromycin, cefazoline and levofloxacin) was against clinical Multi-Drug resistant isolates of Methicillin-Resistant Staphylococcus aureus (MRSA) (Zuo et al, 2012). Several studies indicated that BBR and CLR inhibited hERG currents (Nilsson and Webster, 2014;Schramm et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Staphylococcus aureus (S. aureus) is one of the most common pathogenic bacteria in pyogenic infections, causing systemic infections such as local pyogenic infections, pneumonia, pseudomembranous enteritis, pericarditis and sepsis [1]. In recent years, the emergence of Methicillinresistant Staphylococcus aureus (MRSA), which is resistance to most beta-lactam, has severely limited treatment options [2][3].…”
Section: Introductionmentioning
confidence: 99%